2000
DOI: 10.1046/j.1469-8137.2000.00683.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of root respiration to changes in temperature and its relevance to global warming

Abstract: Global warming over the next century is likely to be associated with a change in the extent to which atmospheric and soil temperatures fluctuate, on both a daily and a seasonal basis. The average annual temperature of the Earth's surface is expected to increase, as is the frequency of hot days. In this review, we explore what effects short-term and long-term changes in temperature are likely to have on root respiratory metabolism, and what impacts such changes will have on daily, seasonal and annual CO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
289
3
10

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(308 citation statements)
references
References 71 publications
6
289
3
10
Order By: Relevance
“…Recent field experiments have shown that as much as half of the soil respiratory carbon release is derived from recent photosynthate (Hö gberg et al 2001;Steinmann et al 2004). An increase in the carbon availability to the root system often causes an increase in root respiration (Atkin et al 2000). Kirschbaum (2006) reported that changes in substrate availability may confound the apparent temperature dependence of SR.…”
Section: Discussionmentioning
confidence: 99%
“…Recent field experiments have shown that as much as half of the soil respiratory carbon release is derived from recent photosynthate (Hö gberg et al 2001;Steinmann et al 2004). An increase in the carbon availability to the root system often causes an increase in root respiration (Atkin et al 2000). Kirschbaum (2006) reported that changes in substrate availability may confound the apparent temperature dependence of SR.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggested that the effects of warming on gross and net primary production, net ecosystem exchange, ecosystem respiration, plant biomass, soil carbon and nitrogen, soil microbial biomass, net nitrogen mineralization and nitrification did not change with the warming duration (Bai et al, 2013;Lin et al, 2010;Lu et al, 2013a;Rustad et al, 2001;Wu et al, 2011) due to the significant, warming-induced increases in the labile carbon and nitrogen availability in the soil (Bai et al, 2013;Lu et al, 2013a;Rustad et al, 2001). In contrast, many studies indicated that the warming duration had a significant negative relationship between the warming effects and plant nitrogen uptake and R s (Atkin et al, 2000;Bai et al, 2013;Melillo et al, 2002), which could be caused by the loss of labile carbon and nitrogen in soils Melillo et al, 2002;Wu et al, 2011). Therefore, whether the effects of warming on carbon and nitrogen were correlated with the warming duration was likely dependent on the conditions of the labile carbon and nitrogen.…”
Section: Influences Of Warming Duration and Raised Soil Temperaturementioning
confidence: 97%
“…Warming stimulated heterotrophic respiration by 11% without clipping and 9% with clipping. Although photosynthetic sensitivity to temperature is smaller than respiration sensitivity (Pearcy and Ehleringer 1984;Atkin et al 2000;Luo 2007), NPP is regulated by many other processes, rendering a possibility that NPP is more sensitive than soil respiration to climate warming.…”
Section: Warming Effects On Ecosystem Carbon Cycling Processesmentioning
confidence: 99%